NUCLEOTIDE SEQUENCE OF LEU - tRNA GENE OF TWO SPECIES DALBERGIA TONKINENSIS AND DALBERGIA COCHINCHINENSIS FOR SPECIMEN IDENTIFICATION IN THE VIETNAM NATIONAL MUSEUM OF NATURE - Hiền, Vũ Thị Thu; Cư, Lưu Đàm; Phòng, Đinh Thị (Vietnam Journal of Biotechnology, 2011)
In Vietnam, Dalbergia tonkinensis and Dalbergia cochinchinensis belonging genus Dalbergia axe rare woody plants with high economic and utilization values. Recently, genome of chloroplast has been extensively studied due to its high conservation and lower frequency of mutations than nuclear DNA. In order to provide a data source at molecular level for identifying specimens, this research was focused on isolating and analysing the sequences of Leu - tRNA (trnL) gene in chloroplast genome, encoding tRNA for leucine transport. Primer pairs Dal2 were designed based on tmL gene sequence of D. foliolosa with assession number EF451106. The amplification fragments with the size of 473 and 423 bp were obtained for D. tonkinensis and D. cochinchinensis, respectively. Sequence analysis of amplified fragments showed that the similarity level between the two was 99.8% and there was difference at only one nucleotide position 56 (T). The comparison with 13 other species in Dalbergia genus revealed that the similarity level in nucleotide sequence oitrnL gene was ranging from 94.6 % to 100% and there were differences at 9 positions: a trinucleotide GGA was inserted at 255 to 257 positions; a pentanucleotide AACTG was deleted from 392 to 396 positions and at position 332, G was replaced by T.